A Study of multicultural awareness among Language Teachers - Esa, Zaleha; Muhamad, Ainon Jariah; S.Dukuly, Varfee (2015)
The population of linguistically and culturally diverse students in tertiary education in Malaysia has increased steadily since the Malaysian Ministry of Higher Education (MOHE) intensified the concept of internationalisation. This changing demographics make it incumbent upon teachers to know their students' cultures.This paper examines multiculturalism as perceived by language teachers at International Islamic University Malaysia.Research has shown that teachers' awareness of multiculturalism of their students will have a direct affect toward the students behaviour and academic outcomes.The aim of this study was to ascertain whether language teachers are aware of multiculturalism. A questionnaire was given to 40 language teachers. The research methodology and some of the findings from the study will be described.